2018
DOI: 10.1111/ppc.12270
|View full text |Cite
|
Sign up to set email alerts
|

Do beliefs about depression etiologies influence the type and severity of depression stigma? The case of Arab adolescents

Abstract: Nurses need to consider the beliefs and attitudes their patients have around depression, as these can influence symptom severity, comprehensive treatment plans, and adherence to provider recommendations. This study provides a better understanding of how depression beliefs affect Jordanian adolescents' attitudes toward depression, which can guide intervention programs to increase awareness about depression and promote treatment utilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Seven (25%) of those that only reported a single component of depression literacy reported knowledge of depression, 12 articles (43%) reported on seeking help for depression and 9 articles reported on stigmatising attitudes towards depression (32%). Eleven of the articles reporting on more than one component of depression literacy (50%) reported on both knowledge and help-seeking, three articles (14%) reported on knowledge and stigmatising attitudes (Dardas et al, 2018;Kelly & Jorm, 2007;Mason, Hart, Rossetto, & Jorm, 2015), one article reported on knowledge, help-seeking and stigmatising attitudes (Sharma, Banerjee, & Garg, 2017), one on knowledge and adequacy of depression literacy (Swartz et al, 2007), one on help-seeking and stigmatising attitudes (Howard, Griiths, McKetin, & Jennifer, 2018), one on knowledge, help-seeking and adequacy of depression literacy (Lam, 2014), one on adequacy of depression literacy and help-seeking (Ruble, Leon, Gilley-Hensley, Hess, & Swartz, 2013). Three articles (14%) reported on adequacy of depression literacy and stigmatising attitudes (Perry et al, 2014;Swartz et al, 2017;Townsend et al, 2017).…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven (25%) of those that only reported a single component of depression literacy reported knowledge of depression, 12 articles (43%) reported on seeking help for depression and 9 articles reported on stigmatising attitudes towards depression (32%). Eleven of the articles reporting on more than one component of depression literacy (50%) reported on both knowledge and help-seeking, three articles (14%) reported on knowledge and stigmatising attitudes (Dardas et al, 2018;Kelly & Jorm, 2007;Mason, Hart, Rossetto, & Jorm, 2015), one article reported on knowledge, help-seeking and stigmatising attitudes (Sharma, Banerjee, & Garg, 2017), one on knowledge and adequacy of depression literacy (Swartz et al, 2007), one on help-seeking and stigmatising attitudes (Howard, Griiths, McKetin, & Jennifer, 2018), one on knowledge, help-seeking and adequacy of depression literacy (Lam, 2014), one on adequacy of depression literacy and help-seeking (Ruble, Leon, Gilley-Hensley, Hess, & Swartz, 2013). Three articles (14%) reported on adequacy of depression literacy and stigmatising attitudes (Perry et al, 2014;Swartz et al, 2017;Townsend et al, 2017).…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…In addition distraction and basic minimal actions such as encourage the suferer to be physically active and suggest seeking help were also endorsed as helpful 'irst aid' for depression by the majority of adolescents in two studies (Essau et al, 2013;Lam, 2014). The common causes of depression reported were normal ups and downs of life, stress, the way in which the suferer had been brought up (Essau et al, 2013;Sharma et al, 2017), cognition (Caporino et al, 2014) and lack of will (Dardas et al, 2018). Adolescents regarded physical activity, distractions, avoidance of the problem or stressful situations, spending time with family and friends on a regular basis and communicating regularly with family and friends as preventive of depression (Essau et al, 2013;Marshall & Dunstan, 2011;Ogorchukwu et al, 2016).…”
Section: Knowledge Component Of Depression Literacymentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the unstandardised beta coefficients in the model for personal stigma, these are also relatively small for the causal beliefs (range 0.38–1.36) compared to the contact groups (range 1.21–4.95). However, Dardas and colleagues who also used the depression stigma scale also found betas between 0.4 and 0.9 for the causal beliefs [ 50 ]. Griffith and colleagues [ 39 ] found betas between 0.15 and 2.37 for various predictors.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 28 studies [7][8][9][10] were included in this review. Of those, 15 studies [14][15][16][17][18][19][20][21][22]25,29,33,[35][36][37] examined mental health problems among Jordanian adolescents only, 3 studies were conducted among Syrian refugees [7,9,26], 3 studies included both Jordanian and Syrian adolescents [8,10,27], 2 studies were conducted among adolescents who resided in refugee camps [24,28], and 5 studies did not specify ethnicity [23,[30][31][32]34]. The sample age ranged from 6-19 years.…”
Section: Studies' Characteristicsmentioning
confidence: 99%